2017
DOI: 10.4103/jfmpc.jfmpc_24_16
|View full text |Cite
|
Sign up to set email alerts
|

Sputum smear grading and treatment outcome among directly observed treatment-short course patients of tuberculosis unit, Jagdalpur, Bastar

Abstract: Introduction:Tuberculosis (TB) is a major global health problem. In 2014, worldwide, 1.5 million deaths were reported from TB. The study was planned to assess sputum smear grading and treatment outcome among TB patients attending tuberculosis unit (TU), Jagdalpur of Bastar district in Chhattisgarh.Materials and Methods:It was a record-based analysis for the year 2014 data from TU, Jagdalpur, Bastar of Chhattisgarh.Statistical Analysis Used:Data entry and analysis were done using STATA/SE 14.1 software.Results:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…It is evidenced that patients with higher sputum AFB grade could have a higher chance of transmitting the disease and developing active TB among contacts than patients with lower grading [ 8 ]. Higher-order smear grading is associated with poor treatment outcome and increased mortality rate due to TB [ 9 ]. Thus, patients with high sputum AFB grade are a potential source of continued TB spread and a nexus for further drug resistance TB development in the community.…”
Section: Introductionmentioning
confidence: 99%
“…It is evidenced that patients with higher sputum AFB grade could have a higher chance of transmitting the disease and developing active TB among contacts than patients with lower grading [ 8 ]. Higher-order smear grading is associated with poor treatment outcome and increased mortality rate due to TB [ 9 ]. Thus, patients with high sputum AFB grade are a potential source of continued TB spread and a nexus for further drug resistance TB development in the community.…”
Section: Introductionmentioning
confidence: 99%
“…In the study of Brahmapurkar K.P. et al ( 2017), with increasing the grade of smear positivity, the number of cases also increased significantly [4] which can be the reason for this inconsistency. Bisognin F. et al (2019) also showed that the frequency of opacity increased with increasing the number of acid bacilli [3].…”
Section: Discussionmentioning
confidence: 98%
“…More time may be needed to clear the heavier load, be it lived or dead bacilli [ 23 ]. Higher bacillary load was associated with poorer treatment outcome and higher mortality rate in tuberculosis [ 24 ]. Another possibility is treatment failure due to multidrug-resistant tuberculosis (MDR-TB) but we did not find many MDR-TB when we traced the sputum culture result.…”
Section: Discussionmentioning
confidence: 99%